Constraining the timing of shale detachment faulting: A geochemical approach - Rowan L. Hansberry (2018)
© 2017 Geological Society of America. K-Ar dating of illite in fault gouges is a useful tool for constraining the timing of brittle fault movement; however, this can be problematic in fault gouges hosted in clay-rich rocks due to the influence of host-rock material. Therefore, this study employs a multianalytical geochemical approach to unravel the influence of host-rock mineralogy, as well as fault zone development, on ages from fault-gouge samples in a shale detachment zone. K-Ar dating of the >2 pm fraction of 6 samples from the Sap Bon Formation detachment zone and associated fault zones in the Khao Khwang fold-thrust belt of centralThailand yielded an age range of 262 ± 5.4 to 208 ± 4.6 Ma. Carbon and oxygen stable isotope analysis along with X-ray diffraction mineralogy indicate that the samples with the youngest K-Ar ages are characterized by higher grade clay mineralogy, and hotter, orogenic fluid temperatures. Using these proxies and comparison to existing geochronology of the study area, we correlated K-Ar illite ages to one of three stages of fault zone evolution: Detrital, diagenetic (burial), and authigenic (fault movement).The youngest K-Ar dates in the Sap Bon Formation are contemporaneous with recently published zircon province data indicating that faulting and detachment zone formation in the Sap Bon Formation were occurring by the mid-Late Triassic, with deformation continuing as late as the Rhaetian.